FDI versus exports: Multiple host countries and empirical evidence - Harald Oberhofer; Michael Pfaffermayr (University of Salzburg, Department of Social Sciences and Economics, 2011)
There are two main options for companies to serve foreign markets: exports and foreign direct investment (FDI). Based on the Helpman, Melitz and Yeaple (2004) model for multiple host countries this paper derives a clear theoretical prediction for the decision between both strategies. A bivariate probit model is estimated using a large data set of European companies to analyze the probability of using one or the other strategy. The empirical evidence indicates that more productive firms less (more) probably use the export (FDI) strategy to serve foreign markets. Moreover, a considerable number of companies use a combination of both strategies to serve foreign markets, which is in line with a multiple country model.
Keywords: C35; D22; F12; 330; Heterogeneous Firms; Exports; Foreign Direct Investment; Multiple Host Countries; Bivariate Probit Estimation